Comparing alternative predictors based on large-panel factor models - Antonello D'Agostino; Domenico Giannone (European Central Bank (ECB), 2006)
This paper compares the predictive ability of the factor models of Stock and Watson (2002) and Forni, Hallin, Lippi, and Reichlin (2005) using a "large" panel of US macroeconomic variables. We propose a nesting procedure of comparison that clarifies and partially overturns the results of similar exercises in the literature. As in Stock and Watson (2002), we find that effciency improvements due to the weighting of the idiosyncratic components do not lead to significant more accurate forecasts. In contrast to Boivin and Ng (2005), we show that the dynamic restrictions imposed by the procedure of Forni, Hallin, Lippi, and Reichlin (2005) are not harmful for predictability. Our main conclusion is that for the dataset at hand the two methods have a similar performance and produce highly collinear forecasts.
Keywords: C31; C52; C53; 330; Factor models; forecasting; Large Cross-Section; Prognoseverfahren; Vergleich; Faktorenanalyse; Theorie